KONSEP PENDIDIKAN HUMANIS DALAM PERSPEKTIF ISLAM - Zainuddin, Riza (EDUKASI: Jurnal Pendidikan Islam, 2015)
Education is an integral part of life and human life, as education alone is the personality of the media in fostering and developing the potential of the human being. Quality multi-dimensional human beings is determined by the educational process, the process is good and right will be significant implications for the quality of its output. Naturally because education is the most basic needs of human beings. Education shall be directed to foster a sense of awareness of divinity and humanity, so as to create a way of life and human life without oppression between human beings with one another. Understanding of the nature, character and potential that exists in humans is one of the educational efforts in shaping the human personality. This of course is done through the process of developing the full potential of human beings, both its physical potential and his spiritual potential. The main runway to realize that education is able to produce quality human, it must rely upon the essential values, which comes from the One who (value divinity) and human values.